Connectivity between serotonin and dopamine systems is altered in Alzheimer's disease: Molecular and cell biology/others. (7th December 2020) - Ceyzériat, Kelly; Gloria, Yesica; Millet, Philippe; Tournier, Benjamin
Abstract: Background: Approximatively half of Alzheimer's disease (AD) patients shows dysfunctions of the dopaminergic (DA) and serotoninergic (5HT) systems, in addition to cognitive impairment. However, the relationships between AD and the time of onset of monoaminergic disorders and their course remain poorly understood. In the present study, we characterized the DA system and the links between the 5HT and the DA systems in the TgF344‐AD rat model of AD. Method: Locomotor activity tests were performed in response to the dopamine receptor 2 (D2R) agonist quinpirole. Quinpirole decreases and activates locomotion according to the dose used, which is attributable to an effect at the pre‐ and post‐synaptic D2R, respectively. The impact of the serotonin receptor 2A (5HT2AR) antagonist MDL100.907 on the quinpirole‐induced locomotion changes was also tested. In vivo SPECT molecular imaging with [ 123 I]IBZM was used for the indirect measurement of DA release in the striatum in response to MDL100.907. The densities of D2R and 5HT2AR receptors were evaluated by in situ autoradiography. Result: Quinpirole stimulated locomotion in wild type (WT, +114, +170 and +65%, at 6‐, 12‐ and 18‐months) and this effect is increased in TgF344‐AD rats at all ages (+340, +300 and +103%). TgF344‐AD rats also showed an increased response to pre‐synaptic dose of quinpirole, at both 6‐ and 12‐months old. These data demonstrated a hypersensitivity of the D2R. The administration of MDL100.907 significantly exacerbated the quinpirole‐induced locomotion in WT (+40%) but not in TgF344‐AD rats, indicating a hypo‐sensitivity of the 5HT2AR. The striatal dopamine release in response to MDL100.907 was significantly higher in WT (25.6%) than in TgF344‐AD rats (10.3%), showing a reduction of the DA system control by the 5HT2AR. This effect was measured at an early stage of the disease (6 months‐old), when amyloid plaques and cognitive disorders were still slight. In addition, the density of 5HT2A receptors was decreased in DA system‐related regions (‐27% in striatum and ‐40% in subtancia nigra), without any modifications on the D2R. Conclusion: TgF344‐AD rats showed functional DA system alterations and a reduction in the connectivity between the 5HT2AR and the DA system that appears early in the course of the disease.